Follower-Centered Perspective on Feedback: Effects of Feedback Seeking on Identification and Feedback Environment - Gong, Zhenxing; Li, Miaomiao; Qi, Yaoyuan; Zhang, Na (Frontiers in Psychology, 2017)
In the formation mechanism of the feedback environment, the existing research pays attention to external feedback sources and regards individuals as objects passively accepting feedback. Thus, the external source fails to realize the individuals’ need for feedback, and the feedback environment cannot provide them with useful information, leading to a feedback vacuum. The aim of this study is to examine the effect of feedback-seeking by different strategies on the supervisor-feedback environment through supervisor identification. The article consists of an empirical study with a sample of 264 employees in China; here, participants complete a series of questionnaires in three waves. After controlling for the effects of demography, the results indicate that supervisor identification partially mediates the relationship between feedback-seeking (including feedback monitoring and feedback inquiry) and the supervisor-feedback environment. Implications are also discussed.